Temperature Effects on the Corrosion Inhibition of Mild Steel in Sulfuric Acid Solution by Acacia senegal Gum with Halide Ions - Emmanuel, Jovine; Buchweishaija, Joseph (Tanzania Journal of Science, 2021)
The effects of temperature on the inhibitive effect of naturally occurring Acacia senegal gum exudate on the corrosion of mild steel in sulfuric acid was studied between 35 and 70 °C using electrochemical impedance spectroscopy and potentiodynamic polarization methods. Findings showed that Acacia senegal gum exudate decreases the corrosion rate of mild steel. The inhibition efficiency declined with raising temperature above 35 °C. The increase in the corrosion rate with increasing temperature was observed for both uninhibited and inhibited systems. Addition of halide ions to the Acacia senegal gum exudate solution enhanced the corrosion inhibition efficiency because of synergistic effects, achieving higher performance with iodide ions as compared to bromide ions. However, the synergistic effects declined above 35 °C up to 70 °C due to temperature effects. It has been observed that increasing temperature adversely affected inhibition efficiencies of both Acacia senegal gum exudate and the synergy between Acacia senegal gum exudate and halide ions. Corrosion rates of mild steel, inhibition efficiencies of Acacia senegal gum exudate and the synergistic effects of halide ions from polarization and impedance measurements were consistent. Keywords: temperature, corrosion, mild steel, synergistic effects, Acacia senegal, gum exudate.